Implementation Of Sharia Management Principles In Islamic Finance - Sabrina Nasution; Chuzaimah Batubara (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
Islamic finance is a rapidly growing field in the world of global finance. This involves developing and implementing financial instruments that comply with sharia principles or Islamic law. These principles include prohibitions against usury (interest), gharar (excessive uncertainty), and maisir (gambling), as well as encouraging social responsibility and transparency in business practices. This study provides a better understanding of the importance of Islamic management in Islamic financial management. The impact of this study is the need for capacity building and increased understanding of sharia governance among stakeholders and regulators. By strengthening sharia governance, sharia financing can continue to grow and contribute significantly to achieving economic development goals according to sharia principles.